2009
DOI: 10.3233/jad-2009-1009
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking, Cognitive Functions in Older Age, Predementia, and Dementia Syndromes

Abstract: Among lifestyle-related factors, low to moderate alcohol drinking has been proposed as a protective factor against the development of age-related changes in cognitive function, predementia syndromes, and cognitive decline of degenerative (Alzheimer's disease, AD) or vascular origin (vascular dementia, VaD) in several longitudinal studies, but contrasting findings also exist. Furthermore, many of these studies were limited by cross-sectional design, restriction by age or sex, or incomplete ascertainment. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
5
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(144 citation statements)
references
References 152 publications
6
127
5
6
Order By: Relevance
“…Several epidemiology studies have suggested that moderate wine intake (250 mL per day) can be beneficial in delaying the onset of cognitive impairments in aging and neurodegenerative diseases [2,3]. In agreement with this, evidences from human randomized controlled trials based on acute supplementations with specific wine compounds reinforce this benefit [4].…”
Section: Introductionsupporting
confidence: 62%
“…Several epidemiology studies have suggested that moderate wine intake (250 mL per day) can be beneficial in delaying the onset of cognitive impairments in aging and neurodegenerative diseases [2,3]. In agreement with this, evidences from human randomized controlled trials based on acute supplementations with specific wine compounds reinforce this benefit [4].…”
Section: Introductionsupporting
confidence: 62%
“…In their systematic review of 49 studies, Panza et al [43] concluded that light to moderate drinking is not harmful to cognition and dementia, although it AlcoHol And tHe elderly. tHe europeAn project VIntAge was not possible to define a specific beneficial level of intake.…”
Section: Dementia and Cognitive Declinementioning
confidence: 99%
“…Research does not indicate that increasing alcohol use results in increased cognitive benefit, rather that abstainers and high-level users perform at similar levels, such that a U shape distribution is often observed [35,36]. …”
Section: Alcoholmentioning
confidence: 99%